Activity and stability studies of H-transfer reduction reactions of aldehydes and ketones over aluminium isopropoxide heterogenised catalysts. Issue 52 (29th November 2022) - Muhammad, Atika; Ismaila, Ammaru; Usman, Bashir Jelani; Di Carmine, Graziano; D'Agostino, Carmine
Abstract : Aluminium isopropoxide Al(O i Pr)3 immobilised on various mesoporous supports (SiO2, TiO2 and γ-Al2 O3 ) was tested for H-transfer reductions of various aldehydes and ketones exhibiting excellent activity and stability. Abstract : Aluminium isopropoxide Al(O i Pr)3 immobilised on various mesoporous supports (SiO2, TiO2 and γ-Al2 O3 ) was tested for H-transfer reductions of various aldehydes and ketones in the presence of 2-propanol as a sacrificial agent. The heterogenised catalysts were characterised by N2 physisorption, XRD, SEM-EDX, FTIR and ICP-OES. The characterisation results show a successful grafting of the homogeneous aluminium isopropoxide catalyst, covalently bound to the solid surface, with high dispersion over the mesoporous supports. The heterogenised catalysts show an excellent catalytic activity with high selectivity towards the desired alcohol product, with performances that are comparable with those of the homogeneous Al(O i Pr)3 catalyst. Al(O i Pr)3 grafted on SiO2 shows higher activity compared to γ-Al2 O3 and TiO2 supported catalysts. The catalysts remain very active after 5 cycles of reuse and no leached Al(O i Pr)3 was found in the reaction mixture, hence showing an excellent stability. The work reported here shows that it is possible to effectively immobilise catalytic functions, usually working in the homogeneous phase, over solid supports, with the resulting heterogenised catalysts keeping the same catalytic activity of the homogeneous counterpart and excellent stability, and with the advantage of being able to recycle and reuse them, without loss of catalytic materials.